Inhibition of spinal nociceptive neurons by microinjections of somatostatin into the nucleus raphe magnus and the midbrain periaqueductal gray of the anesthetized cat - Helmchen, Christoph; Fu, Q. -G.; Sandkühler, Jürgen (Neuroscience letters, 1995)
The effects of somatostatin (SOM) after intravenous application and intracerebral microinjection into the medullary nucleus raphe magnus (NRM) or into the periaqueductal gray (PAG) on the spinal nociceptive transmission was quantitatively studied in the anesthetized cat. Noxious heat-evoked responses of multireceptive lumbar spinal dorsal horn neurons were reversibly depressed to 56.6 ± 9.7% of the control after systemically applied SOM (7 μg/kg i.v.; 7 μg/kg per h infusion rate). At 11 of 14 brainstem microinjection sites in the NRM and PAG, SOM (2.5 μg/μl) attenuated the heat-evoked responses to 58.9 ± 6.2% (n = 5) (NRM) and 64.4 ± 6.3% (n = 6) (PAG) of the control. After microinjection, maximal inhibition was reached within 8-14 min (NRM) or 23-29 min (PAG), respectively. Inhibition was reversible within 60 min after the injection. Thus, SOM has an antinociceptive potency by activating descending inhibition of nociceptive dorsal horn neurons from the NRM and PAG.
Online 24 July 2000
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 28.04.2021